Scaling violations and determination of alpha(s) from jet production in gamma p interactions at HERA - Chekanov, S; Krakauer, D; Loizides, J; Magill, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Basile, M; Bellagamba, L; et al. (2003)
Differential cross sections for jet photoproduction in the reaction ep → e jet X have been measured with the ZEUS detector at HERA using 82.2 pb-1 of integrated luminosity. Inclusive jet cross sections are presented as a function of the jet transverse energy, ETjet, for jets with ETjet > 17 GeV and pseudorapidity -1 <ηjet <2.5, in the γp centre-of-mass-energy range 142 < Wγp < 293 GeV. Scaled jet invariant cross sections are presented as a function of the dimensionless variable xT ≡ 2ETjet/Wγp for (Wγp) = 180 and 255 GeV. Next-to-leading-order QCD calculations give a good description of the measured differential cross sections in both magnitude and shape. The ratio of scaled jet invariant cross sections at the two (Wγp) values shows clear non-scaling behaviour. A value for the strong coupling constant of αs(MZ) = 0.1224 ± 0.0001 (stat.)-0.0019+0.0022(exp.)-0.0042+0.0054(th.) has been extracted from a QCD analysis of the measured dσ/dETjet. The variation of αs with ETjet is in good agreement with the running of αs as predicted by QCD. © 2003 Published by Elsevier Science B.V.